Issue information. Issue 4 (April 2016) - Unknown
Abstract : Cover illustration. A schematic representation of the biological hurdles experienced by therapeutic nanoparticles that must be overcome to deliver drugs to their target. Credit: Peter Allen and Brian Long, UCSB.10.1002/aic.15189